Picture Book-Based Storytelling to Enhance Literacy Among 5–6-Year-Old Children at RA Nurul Islam - Marlis Simarni; Feerlie Mhonthana Indhra; Ani Pajrini (Journal Emerging Technologies in Education, 2026)
Early childhood literacy skills are an important foundation for learning readiness at the next level of education, but in practice, the literacy skills of children aged 5-6 years still require appropriate, interesting, and developmental stimulation. This research aims to improve the literacy skills of children aged 5-6 years through the application of storytelling based on picture books in the literacy corner of RA Nurul Islam. This study uses the Classroom Action Research approach with stages of planning, action implementation, observation, and reflection which are carried out in several cycles. The subject of the study was the children of group B RA Nurul Islam aged 5–6 years. Data is collected through observation, documentation, and assessment of children's performance based on literacy ability indicators which include listening, answering questions, retelling the content of stories, mentioning characters, getting to know new vocabulary, and recognizing simple letters or symbols. The results of the study show that the application of storytelling based on picture books in literacy corners is able to increase children's involvement in learning and gradually improve their literacy skills. Thus, storytelling based on picture books is effectively used as a learning strategy to improve early childhood literacy skills at RA Nurul Islam